THE PARADOX OF DIGITAL ARCHIVAL TRANSFORMATION IN LOCAL GOVERNMENT: A CASE STUDY OF SOUTH BOLAANG MONGONDOW, INDONESIA - Dian Ekawati Moha; Sudarsono; Djamila Podungge (Journal of Economic, Business, and Administration (JEBA), 2024)
The management of government archives is a mandatory administrative affair that serves as the backbone of state accountability and institutional memory. However, peripheral regions in Indonesia often face a "paradox of transformation," where national mandates fail to materialize at the local level. This study aims to evaluate the government archival service policy at the Library and Archives Service of South Bolaang Mongondow Regency using William Dunn’s evaluation framework, focusing on four dimensions: effectiveness, adequacy, responsiveness, and accuracy. Employing a qualitative case study approach, data were gathered through semi structured interviews, non participant observations, and documentary analysis. The findings reveal that archival services in South Bolaang Mongondow currently operate in a state of "strategic neglect," characterized by an ineffective service model, insufficient regulatory instruments (the absence of JRA and Security Classification Systems), low public responsiveness, and fragmented data accuracy. The implementation is hindered by a "triple deficit": a professionalization gap among human resources, severe infrastructure degradation in rented facilities, and systemic budgetary marginalization. Conversely, the regency’s low national ranking (484th) serves as a potential catalyst for reform. The study concludes that bridging the "implementation gap" requires a transition from symbolic formal compliance to substantive professionalization through the adoption of technical SOPs and dedicated fiscal allocation to protect the regency’s administrative heritage.